2015
DOI: 10.3892/ijo.2015.3228
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of IQGAP2 promotes ovarian cancer progression via activating Wnt/β-catenin signaling

Abstract: Abstract. Ovarian cancer is the most lethal gynecologic malignancy and most cases are diagnosed at an advanced stage with metastases; however, the molecular events supporting ovarian cancer development and progression remain poorly understood. In this study, by analysis of the genome-scale DNA methylation profiles of 8 healthy ovaries, 89 ovarian cancers and the corresponding 4 normal ovaries from The Cancer Genome Atlas, we unveiled the abnormalities in gene methylation of ovarian cancers, and found that IQGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 32 publications
2
35
0
1
Order By: Relevance
“…This is in agreement with a previous study, which demonstrated that targeted depletion of 14-3-3β reduces lung cancer cell migration and invasion (31). Activation of Wnt/β-catenin signaling promotes the invasive activities of several types of cancer cells (32,33), while suppression of Wnt/β-catenin signaling inhibits cancer cell invasion (34,35). In the present study, 14-3-3β inhibited β-catenin expression, as well as osteosarcoma cell invasion, suggesting that 14-3-3β may regulate cell invasion through the canonical Wnt signaling pathway.…”
Section: -3-3β Knockdown Suppresses the Expression Of β-Catenin Cysupporting
confidence: 93%
“…This is in agreement with a previous study, which demonstrated that targeted depletion of 14-3-3β reduces lung cancer cell migration and invasion (31). Activation of Wnt/β-catenin signaling promotes the invasive activities of several types of cancer cells (32,33), while suppression of Wnt/β-catenin signaling inhibits cancer cell invasion (34,35). In the present study, 14-3-3β inhibited β-catenin expression, as well as osteosarcoma cell invasion, suggesting that 14-3-3β may regulate cell invasion through the canonical Wnt signaling pathway.…”
Section: -3-3β Knockdown Suppresses the Expression Of β-Catenin Cysupporting
confidence: 93%
“…Our results show that pyrvinium at 100 and 500 nM, which effectively targeted growth and survival, did not affect ATP level in ovarian cancer cells, whereas pyrvinium at 1000 nM slightly decreased ATP level (Supplementary Figure 1), suggesting that pyrvinium does not act on ovarian cancer cells through mitochondrial function inhibition. As Wnt/β-catenin signaling plays an important role in the development of ovarian cancer [5,16,17], we next tested whether pyrvinium acts on ovarian cancer cells through inhibiting Wnt/β-catenin signaling.…”
Section: Resultsmentioning
confidence: 99%
“…IQGAP1 and IQGAP3 have been found to be upregulated in many cancers and promote tumor growth and metastasis [11][12][13][14][15], whereas the role of IQGAP2 is not fully understood in cancers. Most of the reports showed a reduced expression of IQGAP2 in HCC, prostate, gastric and ovary cancer [16][17][18][19], suggesting it to be a tumor suppressor but in couple of studies it was found to be an oncogene too [20,21]. Our previous work also showed reduced expression level of IQGAP2 in breast cancer, using Oncomine data analysis [22].…”
Section: Introductionmentioning
confidence: 87%